Модель машинного навчання для виявлення фейкової складової у новинних текстах - Панкратов, Є. О. (ХНУРЕ, 2023)
In today's world, information technologies play an increasingly important role in people's lives. One of the most important tasks in the field of information technology is the fight against fake information. Now, when a variety of news can be easily distributed through social networks and Internet portals, the problem of detecting fake news is becoming more and more urgent. The rapid spread of these news can lead to serious consequences for society, so there is a need to create effective methods for detecting fake components in news texts. The purpose of this study is to create a machine learning model for detecting fake content in news texts.